Durability of synthetic fiber-reinforced alkali-activated composites - Tanyildizi, Harun; Seloğlu, Maksut (Elsevier, 2023)
Concrete is the second most consumed material in the world after water. One of the main industries producing greenhouse gases is the cement industry. Alkali-activated composites are eco-friendly composites because they are sustainable, use waste materials, and do not contain Portland cement. In this study, the durability properties of synthetic fiber-reinforced alkali-activated composites were examined and compared to the articles in the literature. Steel, glass, basalt, polyvinyl alcohol, and polypropylene fibers, which are the most commonly used synthetic fiber types in the literature, were selected in this study. Furthermore, the high temperature, freeze-thaw, drying–wetting, carbonation, alkali resistance, acid, and sulfate resistances of alkali composites produced using these fibers were investigated. Research findings indicate that alkali-activated composites have the potential for use in civil engineering applications that may be exposed to durability effects. © 2023 Elsevier Inc. All rights reserved.
Keywords: Alkali-activated composites; durability; synthetic fibers